Circuit analysis : theory and practice - Robbins, Allan (Cengage Learning, 2013)
Provides an introduction to the theory, design, and analysis of electrical circuits. Covers direct and alternating current, capacitance, inductance, magnetism, simple transients, transformers, Fourier series, methods of analysis and more. Conceptual material is supported by illustrations and diagrams, as well as step-by-step examples, exercises and hands-on activities.